RNA synthesis precision is regulated by preinitiation complex turnover - Poorey, Kunal; Sprouse, Rebekka O.; Wells, Melissa N.; Viswanathan, Ramya; Bekiranov, Stefan; Auble, David T. (Genome Research, 2010)
TATA-binding protein (TBP) nucleates the assembly of the transcription preinitiation complex (PIC), and although TBP can bind promoters with high stability in vitro, recent results establish that virtually the entire TBP population is highly dynamic in yeast nuclei in vivo. This dynamic behavior is surprising in light of models that posit that a stable TBP-containing scaffold facilitates transcription reinitiation at active promoters. The dynamic behavior of TBP is a consequence of the enzymatic activity of the essential Snf2/Swi2 ATPase Mot1, suggesting that ensuring a highly mobile TBP population is critical for transcriptional regulation on a global scale. Here high-resolution tiling arrays were used to define how perturbed TBP dynamics impact the precision of RNA synthesis in Saccharomyces cerevisiae. We find that Mot1 plays a broad role in establishing the precision and efficiency of RNA synthesis: In mot1-42 cells, RNA length changes were observed for 713 genes, about twice the number observed in set2Δ cells, which display a previously reported propensity for spurious initiation within open reading frames. Loss of Mot1 led to both aberrant transcription initiation and termination, with prematurely terminated transcripts representing the largest class of events. Genetic and genomic analyses support the conclusion that these effects on RNA length are mechanistically tied to dynamic TBP occupancies at certain types of promoters. These results suggest a new model whereby dynamic disassembly of the PIC can influence productive RNA synthesis.